Major knowledge gaps and system barriers to guideline implementation among European physicians treating patients with atrial fibrillation: a European Society of Cardiology international educational needs assessment. Issue 12 (12th March 2018) - Heidbuchel, Hein; Dagres, Nikolaos; Antz, Matthias; Kuck, Karl-Heinz; Lazure, Patrice; Murray, Suzanne; Carrera, Céline; Hindricks, Gerhard; Vahanian, Alec
Abstract: Aims: Guideline-adherent treatment is associated with improved prognosis in atrial fibrillation (AF) patients but is insufficiently implemented in clinical practice. The European Society of Cardiology (ESC) performed a multinational educational needs assessment study among cardiologists, general practitioners/family physicians (GPs/FPs), and neurologists in order to evaluate knowledge and skills of physicians and system factors related to AF care delivery. Methods and results: A total of 561 physicians (294 cardiologists, 131 neurologists, and 136 GPs/FPs) from six European countries participated. This mixed-methods study included exploratory semi-structured qualitative interviews ( n = 30) and a quantitative survey that included two clinical cases ( n = 531). We identified eight key knowledge gaps and system barriers across all domains of AF care. A majority across all specialties reported skills needing improvement to classify AF pathophysiologically, rather than based on duration of episodes, and reported lack of availability of long-term electrocardiogram recording. Skills interpreting the CHA2 DS2 -VASc and the HAS-BLED scores were reported as needing improvement by the majority of neurologists (52% and 60%, respectively) and GPs/FPs (65% and 74%). Cardiologists calculated the CHA2 DS2 -VASc and HAS-BLED scores in 94%/70% in a presented case patient, but only 60%/49% of neurologists and 58%/42% of GPs/FPs did. There was much uncertainty on how to deal with anticoagulant therapy in complex patients. There was also a high disparity in using rate or rhythm control strategies, and indications for ablation. Information delivery to patients and communication between different specialties was often considered suboptimal, while national regulations and restrictions often hamper international guideline implementation. Conclusion: We identified major gaps in physicians' knowledge and skills across all domains of AF care, as well as system factors hampering guideline-compliant care implementation and communication. These gaps should be addressed by targeted educational and advocacy efforts.